The autoimmune susceptibility gene, PTPN2, restricts expansion of a novel mouse adherent-invasive E. coli - Shawki, Ali (Gut Microbes, 2020)
Inflammatory bowel disease (IBD) pathogenesis involves significant contributions from genetic and environmental factors. Loss-of-function single-nucleotide polymorphisms (SNPs) in the protein tyrosine phosphatase non-receptor type 2 (PTPN2) gene increase IBD risk and are associated with altered microbiome population dynamics in IBD. Expansion of intestinal pathobionts, such as adherent-invasive E. coli (AIEC), is strongly implicated in IBD pathogenesis as AIEC increases pro-inflammatory cytokine production and alters tight junction protein regulation – suggesting a potential mechanism of pathogen-induced barrier dysfunction and inflammation. We aimed to determine if PTPN2 deficiency alters intestinal microbiome composition to promote expansion of specific bacteria with pathogenic properties. In mice constitutively lacking Ptpn2, we identified increased abundance of a novel mouse AIEC (mAIEC) that showed similar adherence and invasion of intestinal epithelial cells, but greater survival in macrophages, to the IBD-associated AIEC, LF82. Furthermore, mAIEC caused disease when administered to mice lacking segmented-filamentous bacteria (SFB), and in germ-free mice but only when reconstituted with a microbiome, thus supporting its classification as a pathobiont, not a pathogen. Moreover, mAIEC infection increased the severity of, and prevented recovery from, induced colitis. Although mAIEC genome sequence analysis showed >90% similarity to LF82, mAIEC contained putative virulence genes with >50% difference in gene/protein identities from LF82 indicating potentially distinct genetic features of mAIEC. We show for the first time that an IBD susceptibility gene, PTPN2, modulates the gut microbiome to protect against a novel pathobiont. This study generates new insights into gene-environment-microbiome interactions in IBD and identifies a new model to study AIEC-host interactions.